Sacramental Piety in Luther's Sermon on the Worthy Reception of the Sacrament, 1521 - Ngien, Dennis (Irish theological quarterly, 2005)
Luther's view of justifying Word as God's deed saturates his thinking. God's promises are effective, since they emanate from God and point to him, and in this sense are to be grasped purely by faith, without any human accretions. Faith grasps God's own action done on us according to the efficacious words of Christ's institution so that his divine idioms — righteousness, life and salvation — are communicated to the believer in exchange for the human idioms — sinfulness, death and damnation.